Identification of pre-operative, intra-operative and post-operative risk factors for aspiration pneumonia in patients undergoing abdominal surgery - Kyle John Lindfield; Andrew Little (Global Journal of Perioperative Medicine - Peertechz Publications, 2019)
Objective: To investigate the pre-operative, intra-operative and post-operative risk factors associated with aspiration pneumonia in patients undergoing abdominal surgery. We also aimed to identify the risk-factors that were associated with increased mortality.  Design: Retrospective audit. Setting: Single regional centre located in Australia.  Participants: Patients that were admitted under the general surgery team at a regional hospital in Australia were reviewed to confirm the presence of aspiration pneumonia as a complication during their admission. A total of 19 patients were identified that had a confirmed diagnosis of aspiration pneumonia between December 2013 and November 2016. The medical record of each case of aspiration pneumonia was reviewed in order to identify high-risk features for the development of aspiration pneumonia. Results: The incidence of aspiration pneumonia was found to be 0.3% (19/6431 presentations) between December 2013 and November 2016. The procedure associated with the highest risk of developing aspiration pneumonia was laparoscopic surgery for division of adhesions, in which aspiration pneumonia occurred in 3 of 127 cases (2.3%).  Patients in the non-survivor group were older than the survivor group (81 +/- 12.0 vs 72 +/- 9.9) and had higher American Society of Anaesthesiologists (ASA) physical status score (3.7 +/- 0.6 vs 2.6 +/- 0.6). A history of pre-existing neurological disorders and gastro-oesophageal reflux disorder (GORD) were the most common risk factors for aspiration pneumonia identified. Both of these conditions were present in a total of 8 (42%) patients. Emergency surgical procedures accounted for 14 (74%) of patients that developed aspiration pneumonia in the perioperative setting.  Conclusion: There is a low overall incidence of aspiration pneumonia in patients admitted for gastrointestinal surgery or emergency endoscopy (0.3%). Aspiration with severe consequences tended to occur in patients who were elderly (age > 70-years) and had an ASA physical status score of 3 or more. Pre-existing neurological deficit and GORD were the most common risk factors for the development of aspiration pneumonia. Our study supports the use of a screening tool for the pre-operative identification of patients at risk of pulmonary aspiration. We recommend the implementation of a protocol for managing high-risk patients in the perioperative setting, which includes consideration of the following factors: 1) Prescription of a Proton Pump Inhibitor (PPI) or a Histamine Receptor (H2-R) Antagonist on admission; 2) Implementation of an opioid and sedative sparing technique in the perioperative setting; 3) Consideration of early nasogastric tube insertion, with reinsertion if it is dislodged; 4) Nursing in a 30-degree position with the head up; 5) White board communication tool at the bedside to communicate important dietary information; 6) Multidisciplinary team involvement with speech pathology and physiotherapy input; 7) Speech pathology review prior to eating in the post-operative period if the patient is considered high-risk.